Paleomagnetism of Early Cambrian redbeds on Cape Breton Island, Nova Scotia - Rao, K. V.; Seguin, M. K.; Deutsch, E. R. (Canadian Journal of Earth Sciences, 1986)
Results are reported from steeply dipping red sandstones collected at nine sites (45 samples) of the Lower Cambrian Morrison River and MacCodrum formations on southeast Cape Breton Island, which forms part of the Avalon terrane. Demagnetization studies indicate minimal overlap of stability spectra in thermal, alternating-field, and chemical treatments. A stable component (hematite) with high unblocking temperatures (680 °C) is dominant at all sites. Its mean direction corrected for geologic tilt is D = 281°, I = +32°, k = 97, giving a paleomagnetic pole (pole M) at 20°N, 146°W (dp, dm = 3°, 6°). The corresponding in situ direction is D = 147°, I = +59°, k = 97, with a pole M′ at 2°S, 39°W (dp, dm = 6°, 8°). Poles M and M′ were compared with published Paleozoic poles for the Avalon Zone and cratonic North America to test whether the magnetization originated before or after the Taconic (Ordovician) folding. It could have been acquired during deposition or early diagenesis (Early to Middle Cambrian), in which case the paleolatitude differences between Morrison River–MacCodrum and age-equivalent cratonic sites require a minimum 20° post-Early Cambrian displacement between Avalon Zone and craton. This is, however, difficult to verify, since a fold test is not possible and well-dated Cambrian poles from Avalonia are lacking. Three or four of the many post-Cambrian results from the Avalon and Gander zones were found to be comparable with pole M′, so that alternatively the Morrison River–MacCodrum magnetization could be a postfolding, Late Ordovician–Early Silurian or Late Devonian overprint.